Respostas
respondido por:
2
{[(18+3×2)÷8+5×3]÷6}+{[(5-3+1)÷(-2+5)]}=
{[(18+6)÷8+5×3]÷6}+{[(5-3+1)÷(-2+5)]}=
{[24÷8+5×3]÷6}+{[(5-3+1)÷(-2+5)]}=
{[24÷8+5×3]÷6}+{[(2+1)÷(-2+5)]}=
{[24÷8+5×3]÷6}+{[3÷(-2+5)]}=
{[24÷8+5×3]÷6}+{[3÷-7]}=
{[3+5×3]÷6}+{[3÷-7]}=
{[3+15]÷6}+{[3÷-7]}=
{[3+15]÷6}+0=
{18÷6}+0=
3+0=3
N sei se tá certo blz? ;-;
só sei q demorou pra fzr
jedsonoliveiraowjyyi:
o resultado final é = 4 mais muito obrigado de qualquer forma..
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás